2004
DOI: 10.1007/s11224-004-0733-0
|View full text |Cite
|
Sign up to set email alerts
|

How Has the Bridge Fragment Chosen to Design Charge Transfer Molecular Device?

Abstract: Applying the time-dependent density functional theory (TD-DFT) method the design of molecular logical functions from the dithieno[3,2-b:2 ,3 -d]thiophene (thiophene) and azo-dye Disperse Orange 3 (DO3) molecules joined with various electron-insulator bridges is performed. Based on the results of the investigations, the main design rules for the selection of the bridge fragment between a photoacceptor and photo-donor of a charge transfer molecular device are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In all these investigations the convergence was achieved and the stationary point was found [15,16]. The geometries of the above molecules obtained applying B3PW91 / 6-311G * * basis set exhibit a marked resemblance to the geometrical structure of the supermolecule obtained by B3PW91 / 6-311G and 6-31G.…”
Section: Problem Formulation Investigation Method and Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In all these investigations the convergence was achieved and the stationary point was found [15,16]. The geometries of the above molecules obtained applying B3PW91 / 6-311G * * basis set exhibit a marked resemblance to the geometrical structure of the supermolecule obtained by B3PW91 / 6-311G and 6-31G.…”
Section: Problem Formulation Investigation Method and Resultsmentioning
confidence: 89%
“…This bridge fragment is chosen not accidentally. It has been shown that the bridge fragments not only fix the orientation of the photoelectron donor and photoelectron acceptor molecules with respect to each other but also play a crucial role in the mediation of the electron transfer process by changing electronic properties of the excited state [15].…”
Section: Problem Formulation Investigation Method and Resultsmentioning
confidence: 99%
“…W-7405-ENG-36 and used neutral radical molecules for quantum information processing. [8][9][10][11][12] The aims of this paper are: (i) to design structural and optical properties of the complex molecular photosynthetic system of artificial minimal cell using time dependent density functional theory that has proven to have reasonable agreement with existing experiments at LANL and SDU; * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Tamuliene et al [136] discussed the electronic affect of conjugated rings bridged by -CH=CH-, -CH=N-, and -CH 2 CH 2 -. One would assume that thermochemistry could provide another ken on these bridges.…”
Section: Introductionmentioning
confidence: 99%